MULTI-CRITERIA MODELING FOR THE SELECTION OF CENTRIFUGAL PUMPS DRIVEN BY WIND TURBINES - Author; Conrado Moreno Figueredo; Author; Jorge Lider Macias Ramos; Maria Shirlendy Guerrero Alcivar; Olinda Elizabeth Caicedo Arevalo (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This article is focused on the multi-criteria selection of centrifugal pumps driven by wind turbines, for the supply of water, whose main purposes are to reduce the consumption of electrical energy from the national electricity grid, dependence on fossil fuels and environmental pollution. In this work, a mathematical model composed of a multi-criteria function has been developed, which, through a calculation procedure, makes it possible to select the most technically and economically feasible Wind Turbine / Electro pump combination, applying the exhaustive search method. As economic criteria, the Net Present Value (NPV), the Internal Rate of Return (IRR), the Investment Payback Time (TRI) and the Levelized Cost of Electricity (LEC) are considered. As a technical criterion, the overall efficiency of the system was considered. Finally, the most economically feasible combination was obtained (combination 2). In addition, it is the optimal combination.